Bilateral Deep Brain Stimulation is the Procedure to Beat for Advanced Parkinson Disease: A Meta-Analytic, Cost-Effective Threshold Analysis for Focused Ultrasound. (18th November 2021) - Mahajan, Uma V; Ravikumar, Vinod K; Kumar, Kevin K; Ku, Seul; Ojukwu, Disep I; Kilbane, Camilla; Ghanouni, Pejman; Rosenow, Joshua M; Stein, Sherman C; Halpern, Casey H
Graphical Abstract: